The Effect of Globalization on the Rise of LGBT in Indonesia Through Social Media Networks Instagram and Tiktok - Reza Suhendri Tarigan; Nursapia Harahap (Penerbit Jurnal Indonesia, 2022)
This study discusses deviant sexual behavior In Social networks where LGBT people are looking for a place to realize and look for relationships that take place in certain parties that help and provide all the needs of LGBT organizations through social media. Based on the phenomenon of the emergence of attitudes of LGBT people to the public through Social Media. The author tries to express the phenomenon where LGBT people are not only silent in the era of Globalization as it is today, They also voice their rights in this country through their Social Media. Based on the results of this study, it is hoped that it can provide information and input for the wider community that LGBT people have been very widespread in Indonesia even in the city of Medan, so that we can avoid these actions and the community can refuse and the Medan city government is following up on LGBT people who have appeared themselves on Social Media.